Sensors, actuators, and their interfacesm a multidisciplinary introduction - Ida, Nathan (SciTech Publishing, 2014)
This book "connects the dots" of theory and circuits basics into meaningful systems and real-world applications. Designed to introduce students and practitioners to the principles and applications of sensors and actuators, this book discusses processing hardware and the embedded systems software that connects them